Cerebral Hyperperfusion in a Child with Stroke-Like Migraine Attacks after Radiation Therapy Syndrome - Ardicli, Didem; Gocmen, Rahsan; Oguz, Kader K.; Varan, Ali; Yalnizoglu, Dilek (Neuropediatrics, 2016)
Stroke-like migraine attacks after radiation therapy (SMART) syndrome is a rare complication of cranial radiotherapy characterized by migraine-like headache and transient neurological deficits with typical gyriform enhancement on magnetic resonance imaging (MRI). Potential underlying mechanisms are endothelial damage or dysfunction, vascular instability, vasospasm and, neuronal dysfunction.We report an 11-year-old girl with a primary diagnosis of medulloblastoma presented with acute-onset severe headache and left-sided weakness, 20 months after completing cranial radiotherapy. MRI demonstrated unilateral cortical swelling and concomitant leptomeningeal, gyral contrast enhancement, and MR perfusion imaging showed increased cortical perfusion in the right temporo-parieto-occipital region. Her symptoms resolved spontaneously over several days.SMART syndrome appears to be a reversible, long-term complication of cranial radiotherapy. So far, a limited number of pediatric patients with SMART syndrome have been reported. Prompt recognition of clinical signs and radiological imaging of SMART syndrome may help prevent unnecessary interventions and initiate appropriate diagnostic workup and management.
Keywords: SMART syndrome; children; radiotherapy